a) \(\frac{3}{5}+\frac{2}{7}\times\frac{7}{8}=\frac{3}{5}+\frac{2}{8}=\frac{3}{5}+\frac{1}{4}=\frac{12}{20}+\frac{5}{20}=\frac{17}{20}\)
b) \(1-\frac{3}{4}:\frac{5}{6}=1-\frac{3}{4}\times\frac{6}{5}=1-\frac{18}{20}=1-\frac{9}{10}=\frac{10}{10}-\frac{9}{10}=\frac{1}{10}\)
Cảm ơn bạn rất nhiều!!!!!!!!!!
a) \(\frac{3}{5}+\frac{2}{7}\times\frac{7}{8}\)
\(=\frac{3}{5}+\frac{1}{4}\)
\(=\frac{17}{20}\)
b) \(1-\frac{3}{4}\div\frac{5}{6}\)
\(=1-\frac{9}{10}\)
\(=\frac{1}{10}\)
nhân chia trước
cộng trừ sau
Cảm ơn Lẩu Truyện và Phạm Thành Đông nhiều!!